2013
DOI: 10.4141/cjps2012-333
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile compounds in flowers from four groups of sweet osmanthus (Osmanthus fragrans) cultivars

Abstract: S. 2013. Characterization of volatile compounds in flowers from four groups of sweet osmanthus (Osmanthus fragrans) cultivars. Can. J. Plant Sci. 93: 923Á931. Headspace-solid-phase microextraction (HS-SPME) and gas chromatography-mass spectroscopy (GC-MS) were used to characterize the volatiles in flowers of four cultivar groups of sweet osmanthus (Osmanthus fragrans Lour.), including Thunbergii, Latifolius, Aurantiacus and Semperflorens Groups. A total of 72 volatiles were identified. Volatile compounds and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…As Xin et al (2013) indicated that aroma characteristics in the same cultivar group had a high degree of similarity, three sweet osmanthus cultivars, HBYG, LYJG, and GCDG, each belonging to a different cultivar group and of major economic importance for flower production in central regions of China (Zhou et al, 2006), were chosen for comparing volatiles and aroma-active compounds in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As Xin et al (2013) indicated that aroma characteristics in the same cultivar group had a high degree of similarity, three sweet osmanthus cultivars, HBYG, LYJG, and GCDG, each belonging to a different cultivar group and of major economic importance for flower production in central regions of China (Zhou et al, 2006), were chosen for comparing volatiles and aroma-active compounds in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Collected flowers within each cultivar were mixed well and divided into 2 g samples. All samples were immediately put into airtight polyethylene bags, frozen and stored at −20 °C prior to analysis (Xin et al, 2013). Three biological replicates of each cultivar were used in each experiment.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations